Gestão de revistas científicas acadêmicas: implantação de um Template nas revistas Educação e Educação Especial da Universidade Federal de Santa Maria - Berni, Clenio Perlin (2018)
The research analyzed the insertion of a template for the receipt of articles sent to the periodicals Educação (UFSM) and Special Education Journal of the Education Center of the Federal University of Santa Maria, via Electronic Journaling System (SEER). A template (standardization model of the original articles received) was elaborated, whose purpose was to help the text production by the authors, standardizing the submission of papers. After the implementation of the template, questionnaires were applied to authors, editors, section editors and ad hoc evaluators. The product implemented with the SEER, in addition to facilitating the interpretation of the standards by the authors, expedited the editorial process, since it will no longer be necessary to rework the files that arrive to the sector in different formats. It was concluded that the implantation of the template was effective for the magazines, consolidating the management through institutional portals.